Models for Elasto-electricity and Photovoltaic Material in the Micropower Plant - Strömberg, Lena J. T. (ASEAN Journal for Science and Engineering in Materials, 2022)
In the present paper, the electrodynamic and photovoltaic devices were analyzed. The methods used were modeling of accumulated loads, differential geometry for Solitonials, and generalized Piezo-electricity. Models for dynamic capacitors in the WFB are derived. The analysis is based on observations and experimental results. The experiment was done by providing AC-power background and attaching an NPN-Sun-Catcher. Then, the designed equipment was evaluated in terms of the one-way elasto-electricity and photovoltaic process. The realizations of this designed equipment are suitable for educational purposes. And, this equipment with small encapsulated components operating in higher-power applications can be implemented as realistic solutions for solar-related uses.